Qos-Aware Handover Scheme Using Context Transfer With Link Layer Trigger For Hierarchical Mobile IP - Pillay, Shamini; Khatun, Sabira; Mohd. Ali, Borhanuddin (Penerbit Universiti Sains Malaysia, 2004)
New applications such as VoIP, video on demand and video conferencing, are gaining popularity in the Internet. Although the Internet is based on a best effort delivery mechanism, the introduction of these applications has placed a new demand on the Internet to provide guaranteed Quality of Service (QoS).